2016
DOI: 10.1080/17461391.2016.1266392
|View full text |Cite
|
Sign up to set email alerts
|

No effect of acute and chronic supramaximal exercise on circulating levels of the myokine SPARC

Abstract: Myokines may play a role in the health benefits of regular physical activity. Secreted protein acidic rich in cysteine (SPARC) is a pleiotropic myokine that has been shown to be released into the bloodstream by skeletal muscle in response to aerobic exercise. As there is evidence suggesting that SPARC release may be linked to glycogen breakdown and activation of 5' adenosine monophosphate-activated protein kinase, we hypothesised that brief supramaximal exercise may also be associated with increased serum SPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…We therefore hypothesised and demonstrated that protocols with fewer and shorter sprints result in similar acute signalling responses [ 66 ] and chronic adaptations [ 67 , 74 ] compared with the classic SIT protocol. However, our recent findings that performing single 20-s Wingate sprints three times per week is not a sufficient stimulus for improving O 2 max [ 75 , 76 ] does not provide support for the hypothesis that AMPK-activation following glycogen depletion is responsible for causing increases in O 2 max.…”
Section: Do Proposed Mechanisms Support the Use Of The Classic Sit Prmentioning
confidence: 92%
“…We therefore hypothesised and demonstrated that protocols with fewer and shorter sprints result in similar acute signalling responses [ 66 ] and chronic adaptations [ 67 , 74 ] compared with the classic SIT protocol. However, our recent findings that performing single 20-s Wingate sprints three times per week is not a sufficient stimulus for improving O 2 max [ 75 , 76 ] does not provide support for the hypothesis that AMPK-activation following glycogen depletion is responsible for causing increases in O 2 max.…”
Section: Do Proposed Mechanisms Support the Use Of The Classic Sit Prmentioning
confidence: 92%
“…We have recently provided preliminary data suggesting that a minimum of two sprint repetitions within a training session is required in order to improve VȮ2max (Songsorn et al, 2016;Songsorn et al, 2017;. Reducing the sprint duration in the REHIT protocol would do little to reduce the total training time (the bulk of each training session is spent on the lowintensity warm-up and recovery periods), but if the resulting protocol remains effective at improving VȮ2max it could be beneficial by reducing potential negative affective responses or perceived exertion (Townsend et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Data relating to preanalytical parameters for the quantification of SPARC in the circulation are lacking; it is possible, however, that variations in SPARC levels after exercise are better detected in serum than plasma. Nevertheless, others showed that a single 20s "all-out" cycling sprint induced a significant rise in serum SPARC but that correcting circulating SPARC levels with the exercise-induced changes in plasma volume negated this effect (Songsorn et al, 2017). This finding highlights the importance of measuring hematocrit and hemoglobin levels preand postexercise to verify that the potential exercise-induced alterations in circulating protein concentrations are not due to the changes in plasma volume after exercise (Alis et al, 2015;Dill and Costill, 1974).…”
Section: Sparcmentioning
confidence: 99%
“…This method was chosen, as it is less invasive and stressful than repetitive venipuncture for subjects undergoing eight blood draws over 24 h. However, others have shown that this method of blood sampling could induce local inflammation and affect levels of circulating cytokines to a greater extent than venipuncture (Dixon et al, 2009). In addition, it has been shown that differences in plasma volume can affect the analysis of exercise-induced circulating myokine variations (Songsorn et al, 2017). Since we did not have values for hematocrit and hemoglobin for the time points following the cycling bout, we were unable to measure plasma volume variations as a function of time during the recovery period and therefore could not correct circulating myokine levels to variations in blood composition (Dill and Costill, 1974).…”
Section: Short-comings and Limitationsmentioning
confidence: 99%